The Influence Of Netizens' Comments On Readers' Perception On Tribun Bengkulu's Instagram Account - Serly Oktaviani; Nanda Nanda; Wifi Viola Utama (Jurnal Multidisiplin, 2026)
This study aims to determine the influence of netizen comments on readers' perceptions on the Tribun Bengkulu Instagram account. The development of social media has introduced a new communication pattern that allows audiences not only to receive information but also to respond through the comment section. Those comments can affect how readers understand, evaluate, and form opinions about news. This research uses a quantitative approach with an explanatory research design. Data were collected by distributing questionnaires to 45 respondents who are active Instagram users and have viewed news content on the Tribun Bengkulu Instagram account. Data analysis was performed using simple linear regression, the coefficient of determination, and a t-test. The results show a regression coefficient of 0.728, indicating a strong positive relationship between netizen comments and readers' perceptions. The regression test produced a significance value of 0.000 < 0.05, so H1 is accepted and H0 is rejected. The magnitude of the influence of netizen comments on readers' perceptions, based on the R-squared value, is 72.8%, while 27.2% is influenced by other factors outside the study. These findings indicate that netizen comments play a role in shaping readers' perceptions of news on Tribun Bengkulu's Instagram. Positive comments can increase readers' trust, while negative comments can raise doubt and affect evaluations of the information. User interaction on social media is an important factor in the formation of public opinion in the digital era.